Impact of 2020 EUCAST criteria on meropenem prescription for the treatment of Pseudomonas aeruginosa infections: an observational study in a university hospital. (April 2022) - Munting, Aline; Regina, Jean; Damas, José; Lhopitallier, Loïc; Kritikos, Antonios; Guery, Benoît; Senn, Laurence; Viala, Benjamin
Abstract: Objectives: We aimed to evaluate the impact of the 10th version of European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints table, where most antipseudomonal drugs but meropenem are now categorised as "Susceptible, increased exposure" and labelled I, on meropenem prescription for Pseudomonas aeruginosa infections. Methods: In this retrospective single-centre observational study, we analysed antimicrobial therapies prescribed after susceptibility testing in all consecutive adult patients treated for P. aeruginosa infections between 01.08.2019 and 30.07.2020 in Lausanne University Hospital, Switzerland. We collected epidemiological, microbiological, clinical data, antimicrobial therapy, and infectious diseases specialists (IDs) consultations' data. The primary outcome was the prescription of meropenem to treat P. aeruginosa infections after release of susceptibility testing results. Secondary outcomes were: the use of increased dosage for non-meropenem anti-pseudomonal drugs, and IDs' consultations rates after susceptibility testing was made available. Results: Among the 264 patients included, 40 (15.2%) received meropenem, 3.4% (5/148) before EUCAST update versus 30.2% (35/116) after (p < 0.001). Supervision and counselling from IDs and the use of increased dosages of non-carbapenem antibiotics also increased respectively (40.5% (60/148) vs 62.9% (73/116), P < 0.001 ); (55.5% (76/148) vs 88.9% (72/116), P < 0.001 ). Factors associated with these increments could not be adequately modelled. Conclusions: The change to 2020 EUCAST criteria might be associated with increased odds of meropenem prescription for the treatment of P. aeruginosa infections stressing the need of prescribers' education and the importance of antibiotic stewardship interventions.